Dried-flowers Making - a Potential Cottage Industry in North-east India - Mao, A. A. (Indian Forester, 2000)
North-East India is one of the richest in plant diversity in India and harbours many flowering plants throughout the seasons, which are excellent for making dried-flowers. Driedflowers making can be a potential small cottage industry for the region. This paper presents for the first time a list of plants suitable for dried-flowers making and the techniques of driedflowers making.